Literary Magazines in Cyprus During 2007 - Myaris, George K. (Études helléniques / Hellenic Studies, 2007)
The first literary revues appeared in Cyprus during the first decades of the 20th century. Even though many doubted that the island could sustain two literary publications or more, five literary reviews are published today: the first was launched in 1959, the second a bit later, and the other three since 1989. This article provides background information, characteristic features and other data, although their physionomy will be complete only when they cease publication.